Risk Factors of Vitamin D Deficiency in Chinese Ischemic Stroke Patients: A Cross-Sectional Study - Miao, Hanpei; Zhu, Hanyu; Luan, Xiaoqian; Huang, Guiqian; Chen, Meixia; Yuan, Zhengzhong; Wang, Zhen (Frontiers in Aging Neuroscience, 2021)
Purpose: Lower serum vitamin D has been reported to be associated with stroke. This study aimed to analyze the risk factors of vitamin deficiency in Chinese stroke patients, and further analyze its impact in different gender and their clinical variables. Methods: 982 stroke patients were enrolled. The laboratory parameters such as serum vitamin D, apolipoprotein A-I (ApoA-I) , apolipoprotein B (ApoB), ApoA-I/ApoB, cholesterol (CH), fibrinogen (FIB), blood glucose (Glu), high density lipoprotein (HDL), low-density lipoprotein cholesterol (LDL-C) and triglyceride (TG) were collected and recorded. The severity of stroke was assessed by National Institute of Health Stroke Scale (NIHSS) score. Based on their serum vitamin D level, all patients were divided into three groups: Vitamin D deficiency (<50 nmol/L), Vitamin D insufficiency (≥50-75 nmol/L) and vitamin D sufficiency (≥75 nmol/L) and differences were compared among the three groups. Statistical analyses was done to assess the risk factors for serum vitamin D deficiency in our ischemic stroke patients. Results: Gender, NIHSS, FIB showed significant differences among the vitamin D groups (P <0.001 ~P=0.002). The female gender (OR=2.422, P<0.001), severity of stroke using NIHSS (OR=1.055, P=0.008) and FIB (OR=1.256, P=0.005) were risk factors of vitamin D deficiency in ischemic stroke patients. In subgroup analysis, NIHSS was significantly associated with vitamin D deficiency in the male group (OR=1.087, P=0.002) and a higher FIB group (OR=1.078, P=0.001). Conclusions: The female gender, severity of stroke using NIHSS and FIB were risk factors for vitamin D deficiency in our incident stroke patients. NIHSS was more sensitive to vitamin D deficiency in male ischemic stroke patients. Besides, under higher FIB circumstance, the increasing NIHSS was more related to the vitamin D deficiency. Our report suggests that lower vitamin levels in ischemic stroke may worsen with the severity of incident stroke in females and increase in the concentration of FIB.